Circadian rhythm defects in Prader-Willi syndrome neurons - A. Kaitlyn Victor; Tayler Hedgecock; Chidambaram Ramanathan; Yang Shen; Andrew C. Liu; Lawrence T. Reiter (HGG Advances)
Summary: Prader-Willi syndrome (PWS) is a neurodevelopmental disorder characterized by a spectrum of symptoms, including developmental delay, intellectual disability, and increased risk of autism. PWS is an imprinting disorder caused by the loss of paternal expression of critical genes in the 15q11.2-q13 region, including MAGEL2, SNRPN/SNURF, and SNORD116. PWS patients often suffer from various sleep disorders, including sleep-disordered breathing and central hypersomnolence. Mouse models of PWS also exhibit disruptions in circadian rhythms and sleep. In cultured cells, Magel2 was shown to regulate the expression of Bmal1 and Per2, two core clock genes involved in the circadian rhythm regulatory process. Here, we investigated the circadian clock function in neurons derived from dental pulp stem cells (DPSCs) of PWS patients and neurotypical controls. To study the circadian rhythms of PWS patients in vitro, we introduced the Per2 promoter-driven luciferase reporter (Per2:luc) to these DPSC cell lines to assess their circadian rhythm by bioluminescence. These Per2:luc cells were differentiated for 4 weeks to mature neuronal reporter cell lines, followed by kinetic measurements of luciferase activity over several days. We observed significant differences in circadian period length between PWS neurons and controls. Moreover, treatment with the small molecule longdaysin effectively lengthened the period length of PWS neurons with a shorter period length, as anticipated based on the mechanism of action of this compound. This work lays the foundation for a deeper understanding of PWS pathophysiology and represents a critical first step toward developing high-throughput assays for drug discovery targeting circadian and sleep dysfunction in PWS.